2017
DOI: 10.3390/ijerph14070700
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reproducibility of the Iodine Dietary Intake Questionnaire Assessment Conducted for Young Polish Women

Abstract: The aim of this study was to analyse a designed brief iodine dietary intake questionnaire based on a food frequency assessment (IOdine Dietary INtake Evaluation-Food Frequency Questionnaire—IODINE-FFQ), including the assessment of validity and reproducibility in a group of 90 Polish women aged 20–35 years. Participants collected 3-day dietary records and filled in the IODINE-FFQ twice (FFQ1—directly after the dietary record and FFQ2—6 weeks later). The analysis included an assessment of validity (comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 67 publications
1
25
2
Order By: Relevance
“…Taking it into account, it must be emphasized, that the validity lower than reproducibility may have been observed not due to low accuracy in the case of food frequency questionnaire, but due to a low accuracy of vitamin D intake assessment in the case of dietary record. It also results from the fact, that validity is commonly lower than reproducibility, being observed in several validation studies [ 21 , 32 , 33 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking it into account, it must be emphasized, that the validity lower than reproducibility may have been observed not due to low accuracy in the case of food frequency questionnaire, but due to a low accuracy of vitamin D intake assessment in the case of dietary record. It also results from the fact, that validity is commonly lower than reproducibility, being observed in several validation studies [ 21 , 32 , 33 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reproducibility of the Cro-VIDEO-FFQ questionnaire were based on the definition by Willett and Lenart [ 31 ], and the validation process was conducted according to the same methodology as for the previously conducted validations [ 32 , 33 ]. As the aim of the study was to validate the food frequency questionnaire to analyze the diet against the other method enabling the analysis of diet, the biomarkers of vitamin D status were not included to assess the nutritional status, as well as the vitamin D supplementation that was applied by respondents was not included in the assessment.…”
Section: Methodsmentioning
confidence: 99%
“…All food products meeting the assumed criteria were included in the designed questionnaire, where they were grouped into food product groups characterized by similar folate contents, as is the case in other previously published validation studies [ 24 , 25 , 26 ]. Afterwards, the food products were clustered into 25 food product groups, while vegetables were clustered into 3 separate groups.…”
Section: Methodsmentioning
confidence: 99%
“…The most popular serving sizes were based on the Polish food model booklet [ 30 ], as well as on our own previous studies of food frequency questionnaires [ 24 , 25 , 26 ] and then verified by a dietitian during the pilot research. In the Fol-IC-FFQ these sizes were indicated both in grams and as the described serving sizes.…”
Section: Methodsmentioning
confidence: 99%
“…To further inform the health care provider, a dietary analysis would be useful but is cumbersome; many physicians do not have access to nutritional supports nor is it practical to analyse extensive multi-day diet diaries with every patient. While there are several lengthy validated food frequency questionnaires (FFQ) which can reliably assess iodine intake [14][15][16], a short FFQ validated in UK females of child bearing age could arguably be used simply in a clinical setting by any health care professional [17]. However, the results of this FFQ validation showed that the contribution of dietary iodine was calculated as 12% from fish or seafood and 88% from dairy.…”
Section: Introductionmentioning
confidence: 99%